Song(s) of Struggle : a decolonial reading of Psalm 137 in light of South Africa’s struggle songs: research - Ramantswana, Hulisani (Old Testament Essays, 2019)
This article engages in a decolonial reading of Ps 137 in light of South African songs of struggle. In this reading, Ps 137 is regarded as an epic song which combines struggle songs which originated within the golah community in response to the colonial relations between the oppressor and the oppressed. The songs of struggle then gained new life during the post-exilic period as a result of the new colonial relation between the Yehud community and the Persian Empire. Therefore, Ps 137 should be viewed as not a mere song, but an anthology of songs of struggle: a protest song (vv. 1-4), a sorrow song (vv. 5-6), and a war song (vv. 7-9).
free